Influence of Ni-coating thickness on laser lap welding-brazing of Mg/Ti. (December 2018) - Tan, Caiwang; Zang, Chengwei; Zhao, Xiaoye; Xia, Hongbo; Lu, Qingshuang; Song, Xiaoguo; Chen, Bo; Wang, Gang
Highlights: Join Mg and varied-thickness-Ni-coated Ti using laser welding-brazing process. Ni coating significantly influenced the interfacial reaction products. Thermodynamics calculation explained the interfacial evolution behavior. The optimum fracture load was obtained with appropriate thickness of Ni coating. Abstract: Dissimilar lap joining of magnesium alloy to titanium alloy was performed using Ni coating by laser welding-brazing process. The influence of different Ni-coating thicknesses on microstructure and mechanical properties were investigated. In laser irradiation region, Ti3 Al phase formed at fusion zone/Ti interface. In middle region, Ti3 Al phase still existed at fusion zone/Ti interface, while Mg-Al-Ni ternary IMC generated at fusion zone. In weld toe region, Ti-Ni binary IMC were observed at the interface of fusion zone/Ti. The particles of Mg-Al-Ni ternary compound grew bigger and thickness of Ti-Ni compound layer increased with the increase of Ni-coating thickness. TiNi IMC transformed into (TiNi + Ti2 Ni) mixtures when the Ni-coating thickness exceeded 5.8 μm. Interfacial microstructure evolution was clarified according to thermodynamic calculation results of formation enthalpy and chemical potential. The fracture load first increased and then decreased slightly with increasing coating thickness, the maximum fracture load (2430 N/cm) represented 90% joint efficiency in relation to the Mg base metal. The fracture mode changed from interfacial failure into fusion zone fracture when the Ni-coating thickness was greater than 4.0 μm. The interfacial bonding were relatively low, while the performance of fusion zone fracture was relatively high. Further increase of coating thickness has little effect on the performance deterioration. The bonding mechanism of Mg to Ni-coated Ti were illuminated.